2013
DOI: 10.6065/apem.2013.18.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Boys with precocious or early puberty: incidence of pathological brain magnetic resonance imaging findings and factors related to newly developed brain lesions

Abstract: PurposeBrain magnetic resonance imaging (MRI) findings and factors predictive of pathological brain lesions in boys with precocious puberty (PP) or early puberty (EP) were investigated.MethodsSixty-one boys with PP or EP who had brain MRI performed were included. PP was classified into the central or peripheral type. Brain MRI findings were categorized into group I (pathological brain lesion known to cause puberty; newly diagnosed [group Ia] or previously diagnosed [group Ib]); group II (brain lesion possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
0
27
0
3
Order By: Relevance
“…In addition, the etiology of CPP differs between the genders. While the majority of girls will have idiopathic CPP, boys are more likely to have a pathological source [1, 6]. Risk factors for CPP include a history of international adoption, as well as congenital or acquired central nervous system insults, such as hypothalamic hamartoma, septo-optic dysplasia, tumor, trauma, infection, or ischemia.…”
Section: Etiologymentioning
confidence: 99%
“…In addition, the etiology of CPP differs between the genders. While the majority of girls will have idiopathic CPP, boys are more likely to have a pathological source [1, 6]. Risk factors for CPP include a history of international adoption, as well as congenital or acquired central nervous system insults, such as hypothalamic hamartoma, septo-optic dysplasia, tumor, trauma, infection, or ischemia.…”
Section: Etiologymentioning
confidence: 99%
“…Diagnostic confirmation of CPP relies on the demonstration of pubertal basal and/or GnRH-stimulated LH levels [1, 8]. CPP may result from a central nervous system (CNS) lesion, such as hypothalamic hamartoma, astrocytoma, arachnoid cyst or hydrocephalus [1, 9]. When no cause is identified, it is called idiopathic CPP [1].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, idiopathic CPP is almost 10 times less frequent in boys than in girls [10, 11]. Among boys with CPP, a higher prevalence of CNS lesions has been demonstrated (40–90%), indicating the need for brain magnetic resonance imaging (MRI) in all boys with CPP [1, 9, 11, 12]. However, a recent study suggested that the number of cases of male idiopathic CPP is increasing over time [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sabendo-se que o risco da criança com PPC evoluir com perda estatural na vida adulta é bastante elevado, se seus pais apresentarem estatura abaixo da média populacional, esse agravante assume uma dimensão ainda maior (27) . Quanto menor é a idade de início puberal, maiores são os riscos de tumores como causa de PPC (28) . O início da puberdade aos 6 anos de idade ou menos ocorreu em 60,3% das crianças estudadas na atual pesquisa.…”
Section: Discussionunclassified
“…Como consequência desse retardo, observou-se que, entre aquelas atendidas a partir do segundo ano do aparecimento dos sinais puberais, 83,8% estavam em níveis significativamente mais avançados da puberdade do que as crianças (66,2%) atendidas dentro do primeiro ano do aparecimento dos sinais (p=0,048). Isso mostra como crianças em PPC, quando não tratadas no tempo adequado, sofrem aceleração do processo, exigindo uma maior rapidez nos cuidados, sob pena de maior exposição a conflitos psicológicos, assédio sexual e pior prognóstico para estatura final (27)(28)(29) . Um claro indicador de iniquidade é constatado quando se observa que, entre as crianças atendidas somente no segundo ano após seus pais perceberem os primeiros sinais puberais, 17,8% eram provenientes de famílias com renda mensal de até um salário mínimo, contra 4,3% das crianças atendidas dentro do primeiro ano após o aparecimento dos sinais (p=0,002).…”
Section: Discussionunclassified